1989
DOI: 10.3406/arsci.1989.866
|View full text |Cite
|
Sign up to set email alerts
|

Les marqueurs biogéochimiques : application à l'archéologie

Abstract: Ce travail a consisté à analyser certains marqueurs biogéochimiques pour l'étude de paléoenvironnements d'intérêt archéologique. Le choix des molécules étudiées par chromatographie en phase gazeuse (CPG) et en couplage chromatographie- spectrométrie de masse (CPG/SM) s'est porté sur des constituants lipidiques tels que les alcanes, les acides gras (saturés, insaturés, ramifiés) et les stérols en raison de leur stabilité chimique et de leur ubiquité dans le règne végétal et animal. Certains critères nous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The work is highly complementary to earlier investigations which have shown that coprostanol (5 -cholestan-3 -ol) has considerable potential as an indicator of human inputs into archaeological soils and sediments (Knights et al, 1983;Pepe et al, 1989;Bethell et al, 1994). The approach used here was to study soils sampled from the Butser Farm experimental plot used for cultivation of wheat for a period of 13 years.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The work is highly complementary to earlier investigations which have shown that coprostanol (5 -cholestan-3 -ol) has considerable potential as an indicator of human inputs into archaeological soils and sediments (Knights et al, 1983;Pepe et al, 1989;Bethell et al, 1994). The approach used here was to study soils sampled from the Butser Farm experimental plot used for cultivation of wheat for a period of 13 years.…”
Section: Discussionmentioning
confidence: 67%
“…Published work on molecular markers in the soil includes the identification of human faecal lipids from Roman ditch sediments (Knights et al, 1983); analysis of lipids from excavations in Paris (Pepe et al, 1989;Pepe & Dizabo, 1990); and attempts to locate kill/butchery areas at a buffalo jump site in North America (Dormaar & Beaudoin, 1991). Recent work has involved the use of lipids, using gas chromatography (GC) and combined gas chromatography/mass spectrometry (GC/MS), in the study of ''biomarkers'' of human faecal deposition (Bethell et al, 1994;Evershed & Bethell, 1996).…”
mentioning
confidence: 99%
“…A more rigorous identification of faecal matter can be achieved by analysing faecal biomarkers (e.g. Bethell et al, 1994;Knights et al, 1983;Pepe et al, 1989;Pepe and Dizabo, 1990). These markers are organic compounds derived from a faecal source, which retain their chemical structure during diagenesis (Bull et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…During the recent past, a variety of lipid patterns and compounds have been described to be diagnostic for different organic materials. They provide the potential to reflect soil management practises in soil organic matter (Pepe and Dizabo, 1989;Bethell et al, 1994;Evershed et al, 1997;Simpson et al, 1998;Bull et al, 1999a;.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of lipids in soils became an established application in palaeoenvironmental and archaeological research (Knights et al, 1983;Pepe and Dizabo, 1989;Evershed, 1993;Bethell et al, 1994). Soil lipids derive mainly from plants or microorganisms (Dinel et al, 1990).…”
Section: Introductionmentioning
confidence: 99%